Can Artificial Intellegence Push Translators Out of Society? (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The role of artificial intelligence in terms of literal translation and oral interpretantion. There was given several comparisons of the texts of online and human translators. Also, key aspects of why human factor is so crucial in translation.